DETERMINAN PENCEGAHAN FRAUD DIMEDIASI OLEH AUDITOR INTERNAL APIP - Adinda Priski Dhea Asiyanti; Ihyaul Ulum; Agung Prasetyo Nugroho Wicaksono (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2023)
In Indonesia, fraud is better known as corruption. Law Number 20 of 2001 explains that corruption is an action that harms the common interest or the wider community for the benefit of personal interests and/or certain groups. Fraud is usually triggered by a weak control system and lack of supervision in financial management. Problems regarding fraud have been found in the remaining facilitator recruitment funds, as well as accountability for financial reporting of village funds. Sampling in this study used a type of sampling, namely probability sampling with a simple random sampling technique and using the Slovin formula in determining the sample size. The data analysis technique used is SEM PLS (Partial Least Squares) data analysis using Smart PLS 3.0 software. From the results of this research, accountability has no effect on fraud prevention, while village apparatus competency and APIP internal audit supervision have a positive and significant effect on fraud prevention .